2017
DOI: 10.1111/1462-2920.13644
|View full text |Cite
|
Sign up to set email alerts
|

The expression of Longus type 4 pilus of enterotoxigenic Escherichia coli is regulated by LngR and LngS and by H‐NS, CpxR and CRP global regulators

Abstract: Enterotoxigenic Escherichia coli produces a long type 4 pilus called Longus. The regulatory elements and the environmental signals controlling the expression of Longus-encoding genes are unknown. We identified two genes lngR and lngS in the Longus operon, whose predicted products share homology with transcriptional regulators. Isogenic lngR and lngS mutants were considerably affected in transcription of lngA pilin gene. The expression of lngA, lngR and lngS genes was optimally expressed at 37°C at pH 7.5. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 72 publications
(125 reference statements)
0
28
0
Order By: Relevance
“…The regulatory role of the CpxRA TCS in the expression of several pili of pathogenic E. coli including the BFP, curli, P pili, and Longus has been well-documented (Hung et al, 2001;Hernday et al, 2004;Nevesinjac and Raivio, 2005;De la Cruz et al, 2017). It is not surprising that biofilm was affected in the ΔcpxA mutant since production of T1F and flagella were also affected and these components contribute significantly to biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The regulatory role of the CpxRA TCS in the expression of several pili of pathogenic E. coli including the BFP, curli, P pili, and Longus has been well-documented (Hung et al, 2001;Hernday et al, 2004;Nevesinjac and Raivio, 2005;De la Cruz et al, 2017). It is not surprising that biofilm was affected in the ΔcpxA mutant since production of T1F and flagella were also affected and these components contribute significantly to biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation of cpxRA in enteropathogenic E. coli (EPEC) affects the production of type IV bundle-forming pili, impairing adherence to epithelial cells (Nevesinjac and Raivio, 2005), while an enterohemorragic E. coli (EHEC) O157:H7 cpxA mutant is defective in cell adherence due to the alteration in the secretion of type 3 secretion effectors and components (De la Cruz et al, 2016). The production of Longus, a type IV pilus of enterotoxigenic E. coli, was recently demonstrated to be regulated by the CpxRA TCS (De la Cruz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work represents the first investigation of the T6SS function in the Enterobacter genus and it describes the different roles of two T6SS in the pathogenicity of E. cloacae ATCC 13047. Several studies have demonstrated that environmental conditions are important for the differential expression of genes involved in the bacterial virulence (Dong and Mekalanos, 2012;Blair et al, 2013;De La Cruz et al, 2017;Ares et al, 2019). We showed that TSB and DMEM growth media stimulated the expression of E. cloacae T6SS-1 and T6SS-2, respectively, indicating that gene expression in both T6SSs is regulated by specific environmental cues, most likely compounds present in the culture medium.…”
Section: Discussionmentioning
confidence: 64%
“…Host and environmental stimuli such as temperature, osmolarity, pH, and carbon source are sensed by ETEC to regulate the expression of virulence factors such as toxins and pili (Kansal et al, 2013; Munson, 2013; Haycocks et al, 2015; De La Cruz et al, 2017). However, only in a few cases the influence of environmental and nutritional factors on the expression and production of some of the ETEC’s CFs has been reported.…”
Section: Introductionmentioning
confidence: 99%